The Construction of Conceptual Metaphors in the Discourse of BIPA Learners: A Cross-Cultural Thematic Study - Istiqomah Putri Lushinta; Eri Kurniawan; R. Dian Dia-an Muniroh (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Metaphorical competence has been recognized as essential to advanced communicative proficiency in a second language, yet Indonesian as a Foreign Language (BIPA) has remained entirely absent from this research landscape, despite rapid global growth in learner numbers across typologically diverse language backgrounds. This study synthesizes internationally recognized empirical studies published between 2010 and 2025 on how second-language learners construct and use conceptual metaphor in discourse, with direct implications for BIPA instruction. Analysis was conducted using a Cross-Cultural Cognitive Discourse Analysis framework integrating Conceptual Metaphor Theory, Critical Metaphor Analysis, and van Dijk's sociocognitive approach, with metaphor identification following the MIPVU procedure. Three dominant patterns were identified. First, learners systematically transfer conceptual schemas from their first language into Indonesian discourse, producing utterances that are grammatically correct but culturally incongruent conceptual fluency failure with the extent and type of transfer varying predictably by language family. Second, orientational metaphors show significant cross-cultural variation: schemas such as POWER IS UP operate universally, while others are culture-specific, and processing them in a second language incurs measurable cognitive load. Third, ontological metaphors encoding distinctly Indonesian concepts gotong royong, musyawarah-mufakat, and rukun are systematically distorted when reconstructed through first-language conceptual systems, producing reductions that eliminate their most fundamental ontological properties. On this basis, the study proposes two contributions: the Universal-Relative Metaphor Principle, which resolves the universalism-relativism debate by locating each position at a different level of analysis, and the Cross-Cultural Metaphor Competence Framework, a four-dimensional hierarchical pedagogical model for BIPA. This study thus represents the first data-grounded contribution to metaphor theory and pedagogy in the BIPA context.